Herramientas visuales y su aporte en el aprendizaje de la geografía a estudiantes de la unidad educativa Aurora Estrada y Ayala, cantón Babahoyo, Provincia de los Ríos - Mora Macias, Wendy Katherine (2016)
Today we talk about the necessary transformation of educational models, today there is lot of literature on learning theories that could be effective at the time they applied in the educational process; however, very few actually make the theory work in teaching practice and much less if the field is the area of geography. In Ecuador, even with little access to visual tools, the Society Technology Computer and Communication have not been exempt from this influence, in the Educational Unit "Aurora Estrada and Ayala" are notable lack of tools visual and contribution in learning geography, which prevents real development of education student learning and hinders the role of teachers in their work, even more so knowing that there are various visual tools in this age of technological advances, same that would help improve the learning of students in the area of geography, `so you agree to analyze the contribution of visual students of the Education Unit Aurora Estrada and Ayala to train teachers and improve tools learning area school geography.